EVALUASI METODE PENGERINGAN TERHADAP KUALITAS TEPUNG PISANG TONGKA LANGIT SEBAGAI BAHAN PENYUSUN PANGAN FUNGSIONAL - Salwa Syafira, Annisa
Pisang tongka langit (Musa troglodytarum L.) is a type of banana found in Eastern Indonesia, particularly in the Maluku Islands. This fruit has a higher antioxidant activity compared to other bananas, with a total carotenoid content reaching 6360 ?g/100 g. Tongka Langit banana (TLB) can generally be consumed directly, but it is not very popular due to its sour taste. Both the pulp and peel of TLB can be processed into flour as an alternative ingredient for functional food. This study aims to determine the effect of drying temperature and acid treatment on the quality of TLB pulp flour and peel flour produced. The main analysis was conducted on the antioxidant activity of the flour. Proximate content analysis, total carotenoid, and determination of shelf life were carried out as flour characterization. The drying method was performed using a food dehydrator with temperature variations of 40°C, 50°C, and 60°C and with variations of citric acid pre-treatment at 0.5% w/v and without acid pre-treatment. White bread was made to determine the feasibility of the resulting flour as an alternative food ingredient. The results showed that drying temperature and acid treatment significantly affected antioxidant activity (p < 0.05), with the best drying obtained at 0.5% w/v citric acid pre-treatment at 50°C. The antioxidant activity values for TLB pulp and peel flour were 64.27% and 82.51%, respectively. Proximate and carotenoid characterization yielded values for moisture, ash, crude fiber, protein, fat, carbohydrate, and total carotenoids for TLB pulp flour at 7.74%; 3.92%; 12.57%; 1.30%; 1.73%; 82.71%, and 22.72 mg/100 g, respectively, and for TLB peel flour at 8.32%; 9.59%; 16.51%; 1.73%; 1.81%; 77.68%, and 84.39 mg/100 g, respectively. The shelf life of the pulp and peel flour stored at 25°C was 7.75 months and 25.07 months, respectively. The white bread made using TLB pulp flour in a 1:1 ratio with wheat flour was more acceptable to the panelists.